Effect of PPARγ Inhibition during Pregnancy on Posterior Cerebral Artery Function and Structure - Chan, Siu-Lung; Chapman, Abbie C.; Sweet, Julie G.; Gokina, Natalia I.; Cipolla, Marilyn J. (Frontiers in Physiology, 2010)
Peroxisome proliferator-activated receptor-γ (PPARγ), a ligand-activated transcription factor, has protective roles in the cerebral circulation, and, is highly activated during pregnancy. Thus, we hypothesized that PPARγ is involved in the adaptation of cerebral vasculature to pregnancy. Nonpregnant (NP) and late-pregnant (LP) rats were treated with a specific PPARγ inhibitor GW9662 (10 mg/kg/day, in food) or vehicle for 10 days and vascular function and structural remodeling were determined in isolated and pressurized posterior cerebral arteries (PCA). Expression of PPARγ and angiotensin type 1 receptor (AT1R) in cerebral (pial) vessels was determined by real-time RT-PCR. PPARγ inhibition decreased blood pressure and increased blood glucose in NP rats, but not in LP rats. PPARγ inhibition reduced dilation to acetylcholine and sodium nitroprusside in PCA from NP (p<0.05 vs. LP-GW), but not LP rats. PPARγ inhibition tended to increase basal tone and myogenic activity in PCA from NP rats, but not LP rats. Structurally, PPARγ inhibition increased wall-thickness in PCA from both NP and LP rats (p<0.05), but increased distensibility only in PCA from NP rats. Pregnancy decreased expression of PPARγ and AT1R (p<0.05) in cerebral arteries that was not affected by GW9662 treatment. These results suggest that PPARγ inhibition had significant effects on the function and structure of PCA in the NP state, but appeared to have less influence during pregnancy. Down-regulation of PPARγ and AT1R in cerebral arteries may be responsible for the lack of effect of PPARγ in cerebral vasculature and may be part of the vascular adaptation to pregnancy.